Sweet Briar goes to school - Wilson, Karma; Pham, LeUyen (New York : Puffin Books, 2005)
The other animals at school make fun of Sweet Briar because she is a skunk and has a strong smell, until she uses her scent to chase away a hungry wolf.
K-3
Accelerated Reader AR
Keywords: Skunks -- Fiction; Animals -- Fiction; School stories